Schaum's outline of theory and problems of differential equations in SI metric units - Ayres, Frank (New York : McGraw Hill Education, 1972)
This book is designed primarily to supplement standard texts in elementary differential equations.
Includes index.
Keywords: DIFFERENTIAL EQUATIONS -- PROBLEMS, EXERCISES, ETC